DRILLING DOWN: AN EXAMINATION OF THE BOOM-CRIME RELATIONSHIP IN RESOURCE BASED BOOM COUNTIES - R. Ruddell; D. S. Jayasundara; R. Mayzer; T. Heitkamp (Russian Journal of Economics and Law)
Objective: to examine the boom-crime relationship in resource-based boom counties, and to propose socio-economic and legal measures to reduce the boomtown effect.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors that determined the choice of the following research methods: formal-logical, comparative-legal, survey, interview, focus groups, generalized least squares method.Results: The expansion in natural resource development in rural communities has led to a number of social problems in these places. The media, community stakeholders, as well as law enforcement and human service personnel have reported that the rapid growth in these communities leads to increased crime and other social ills. In order to better understand the boom-crime relationship, index crimes in oil and natural gas producing counties in Montana and North Dakota were examined. Comparison of 2012 crime rates in a matched sample of counties revealed that crime rates were higher in oil-impacted counties. A pre-post analysis found that violent crime in boom counties increased 18.5% between 2006 and 2012 while decreasing25.6% in a matched sample of counties that had no oil or gas production. Inconsistent with the media portrayal of these communities as a new "wild west" we did not find a significant association between oil or natural gas production and property or violent crime in a series of OLS regression models. Scientific novelty: for the first time the article uses index crimes in oil and natural gas producing counties in Montana and North Dakota to reveal the association between the rapid growth of towns and the crime rates.Practical significance: the main provisions and conclusions of the article can be used in research and educational activity, as well as for predicting the social-economic development of boomtowns.